2000
DOI: 10.1016/s0022-5347(05)67361-2
|View full text |Cite
|
Sign up to set email alerts
|

Penile Fracture in Kermanshah, Iran: Report of 172 Cases

Abstract: Patient misinformation about penile tissue properties is the main explanation for the high incidence of penile fracture. Cavernosography, and urethrography and intraoperative urethral catheterization are not routinely needed, as diagnosis can be made clinically. Preoperative and postoperative use of antibiotics, and a uniform surgical plan regardless of delay in presentation are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
127
0
16

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(157 citation statements)
references
References 9 publications
9
127
0
16
Order By: Relevance
“…This rate is highly inferior to those reported in the United States and Europe which range from 10 to 30%, but it resembles to those reported in Asia and the Middle East. [5][6][7][8][9] Several causes of penile fracture have been reported, including traumatic coitus, violent penile manipulation, masturbation or rolling over in bed onto an erect penis. Among these causes, sexual intercourse leads the most to urethral rupture, given the high violence of the trauma in this situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate is highly inferior to those reported in the United States and Europe which range from 10 to 30%, but it resembles to those reported in Asia and the Middle East. [5][6][7][8][9] Several causes of penile fracture have been reported, including traumatic coitus, violent penile manipulation, masturbation or rolling over in bed onto an erect penis. Among these causes, sexual intercourse leads the most to urethral rupture, given the high violence of the trauma in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13 Others, however, consider that routine urethrography is unnecessary, 9 as well as magnetic resonance imaging, which has been shown to be accurate in diagnosing urethral lesions. 14 In our series, we directly adopted an interventional approach since urethral rupture is often located at the same level as corporal tear.…”
Section: Management Of Penile Fracturesmentioning
confidence: 99%
“…On the other hand, in the Middle East, the majority of cases were reported to result from penile manipulations during masturbation. 10,19 The majority of our study population reported sexual intercourse as the cause of their penile fracture. To our knowledge, there is no study in the current literature describing the physical characteristics (weight, height, and BMI) of penile fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…Complications such as penile curvature, fibrotic plaque formation and painful erection are largely prevented, sexual functions are preserved and hospitalization period is substantially shortened with the early (within 24 h after the penile fracture) surgical repair. 18,19,21 Although early surgical repair has promising outcomes, complications such as penile nodules, curvatures and sensory loss may be observed in some cases. In our series, the incidence of palpable penile nodules was determined as 5% and both penile curvature and temporary penile skin sensory loss was observed in 2% of the cases.…”
Section: Discussionmentioning
confidence: 99%